Pelatihan Pemanfaatan Aplikasi Design Online Canva dalam Meningkatkan Pemasaran Online pada UMKM pemula di lingkup Mahasiswa Universitas Tangerang Raya - Siahaan, Febri Sari; Ahmad Rasyiddin; Yunita Nur Afni (Universitas Tangerang Raya, 2024)
This research aims to evaluate the effectiveness of training in using the online design application Canva in improving online marketing for beginner MSMEs among students at Tangerang University. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews, observation and documentation of training participants. The research results show that using Canva significantly improves the visual quality of marketing content, which has a positive impact on increasing engagement and product sales. This research provides a practical contribution to the development of online marketing strategies for budding MSMEs and offers guidance for educational institutions in developing similar training programs.